The influence of people income on vegetables consumption in Romania - Raluca Andreea Ion (Agrarian Economy and Rural Development - Realities and Perspectives for Romania. 9th Edition of the International Symposium, November 2018, Bucharest, 2018)
The article analysis the people income influence of vegetables' consumption, assuming that the consumption of vegetables increases along with income growth. The paper tries to answer the question what are the direction and the intensity of income influence on vegetables' consumption? In pursuing this question, data related to income and vegetables'consumption have been analysed using the regression models. The results show that 1-unit change in the level of income leads to 0.720 units change in the level of vegetablesconsumption. The consumption of vegetables reacts evident to changes in the level of income, as compared to the consumption of fruits. The topic of research and the findings are relevant, because of vegetables' importance for human health, due to their content in micro and macro nutrients. Is also rises awareness on the determinants of vegetables' consumption, and on the extent to which people income plays a role in food choices.
Keywords: Q13; 330; vegetables; market; self-consumption; people income